2013
DOI: 10.1111/aos.12270
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve hypoplasia in children and adolescents; prevalence, ocular characteristics and behavioural problems

Abstract: ABSTRACT.Purpose: To report prevalence, ocular characteristics and coexisting behavioural problems in children and adolescents with optic nerve hypoplasia (ONH), which is a common cause of visual impairment in children in western countries, often associated with neurological or endocrinological problems and where autism has been reported in severe cases with blindness. Methods: This is a population-based cross-sectional study of patients <20 years of age who had been diagnosed with ONH and lived in the county … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
(48 reference statements)
1
41
0
1
Order By: Relevance
“…The median score of patients with unilateral ONH was comparable to that in the current study, while patients with bilateral ONH scored higher (Tear Fahnehjelm et al. ). While there were no bilateral MGDA patients in this study for comparison, a report by Nawratzki and co‐workers described a patient with bilateral MGDA and autism (Nawratzki et al.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The median score of patients with unilateral ONH was comparable to that in the current study, while patients with bilateral ONH scored higher (Tear Fahnehjelm et al. ). While there were no bilateral MGDA patients in this study for comparison, a report by Nawratzki and co‐workers described a patient with bilateral MGDA and autism (Nawratzki et al.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of optic nerve hypoplasia has previously been reported as 17.3/100 000 in patients <18 years of age in the same population (Tear Fahnehjelm et al. ) showing that MGDA is a less common condition. The frequency of intracranial anomalies and vascular malformations in patients with MGDA, hitherto not reported, was 25%.…”
Section: Discussionmentioning
confidence: 83%
“…The diagnosis is clinical and characterised by a thin optic nerve with a reduced number of retinal ganglion cell axons in one or both eyes. We have previously reported that the prevalence of ONH in children was 17.3/100 000 in the county of Stockholm and unilateral in 45% of the patients .…”
Section: Introductionmentioning
confidence: 99%
“…Optic nerve hypoplasia (ONH) is a developmental disorder in which there is a small optic nerve head and/or a reduced number of fibres in the optic nerve. It is the most common congenital optic nerve disorder and is a leading cause of childhood vision impairment in both the US and Europe, affecting as many as 12% of visually impaired children …”
Section: Introductionmentioning
confidence: 99%